Development of a Learning Activity Package Integrated with MCIS Instructional Approach to Address Misconceptions About Light Ray Diagrams Among Grade 9 Students During the First Semester of the 2024 Academic Year - Yamtim, Patsadawan; Wutchana, Umporn (Journal of Buddhist Education and Research (JBER), 2025)
The research aims to (1) to investigate misconceptions in ray diagram construction for light among Grade 9 students, (2) compare the pre-test and post-test learning achievements of students who were taught using learning activities integrated with the MCIS instructional model, and (3) study the satisfaction of students who participated in the learning activities integrated with the MCIS instructional model. The target groups for the study include: Group 1 – 25 students from Grades 9-12, selected through cluster random sampling. Research instruments included (1) a misconception assessment tool, (2) a learning activity set, (3) an MCIS learning plan, (4) an achievement test, and (5) a satisfaction questionnaire. Data were analyzed using mean, percentage, standard deviation, and dependent sample t-tests. The results showed that (1) most students had no conceptual understanding (NU), followed by those with scientific misconceptions (SM) and a smaller group with partial scientific understanding combined with misconceptions (SM). (2) Post-test learning achievement was significantly higher than pre-test achievement at the 0.05 level of significance. (3) The overall satisfaction of students with the learning activities integrated with the MCIS instructional model was at the highest level (M = 4.53, SD = 0.51).ส่วนบนของฟอร์ม